GUIDELINES FOR THE PREVENTION OF DRUG PROBLEMS FOLLOW UP ON SUSTAINABLE COMMUNITY OPERATIONS - Kanyajit, Sunee; Sokantat, Natthapon; Limwongsakul, Korkieat (Journal of MCU Nakhondhat, 2023)
This research aims to 1) study key factors of successful operation in sustainable community project to solve drug problems in the community and 2) to develop guideline from sustainable community operation in terms of prevention and solve of drug problems. This is qualitative research and in - depth interview was a tool to gather data. The samples were involved in sustainable community operation that consisted of 30 participants of the project, 30 officers, 30 village/community committee and 30 people in community area. This research was employed technique of content analysis to examine data. It found that firstly, successful factor is collaboration in the same direction. Then, another factor is the budget that is important in term of project implementation and in terms of treatment. These factors can be used to develop guidelines for project implementation, particularly making confidence to people in the community. This considers to be the importance of first step in reassuring the public in non - prosecution. Also, clear procedures must be publicized, especially post - procedures of treatment and guidelines for life support of reentry in society. Finally, people and community leaders in the community must be robust and continue the project on their own track by comprehension in community context and basics of the people in the community. In addition, a precise goal must be established and direction of the project must be clear and as well as a systematic follow - up and evaluation.